2014
DOI: 10.1111/rda.12288
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of the Reproductive Tract, Spermatogenesis, Daily Sperm Production and Major Seminal Plasma Proteins of Tropically Adapted Morada Nova Rams

Abstract: This study describes the reproductive parameters of Morada Nova rams, a breed of hair sheep from Brazil and with unique adaption to tropical environments. At 42 weeks of age, 15 rams were subjected to semen collection and, 1 week later, animals were slaughtered for collection of testes, epididymis and accessory sex glands. We conducted 2-D electrophoresis of seminal plasma proteins and major spots of stained gels were identified by LC-MS/MS. Total RNA was isolated from testis, epididymis and vesicular glands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
2
5
0
Order By: Relevance
“…The S/PQ ratio obtained in the control group corroborates the findings of Sousa et al (2014) in Morada Nova sheep, whereas the S/Ar ratio was higher than that reported by the authors. The total production of PQ is usually adjusted numerically to support the capacity of Sertoli cells, causing the degeneration of large numbers of cells ( De Rooij and Lok, 1987 ).…”
Section: Discussionsupporting
confidence: 89%
“…The S/PQ ratio obtained in the control group corroborates the findings of Sousa et al (2014) in Morada Nova sheep, whereas the S/Ar ratio was higher than that reported by the authors. The total production of PQ is usually adjusted numerically to support the capacity of Sertoli cells, causing the degeneration of large numbers of cells ( De Rooij and Lok, 1987 ).…”
Section: Discussionsupporting
confidence: 89%
“…The T levels observed in this study are similar to the values reported in Saint Croix rams in Mexico (Aguirre et al 2007) and Morada Nova rams in Brazil (Sousa et al 2014). However, when raised in tropical regions, the effect of season on T is more nutritionally dependent, especially in the case of cross-breeding with wool breeds (Zhang et al 2005;Cárdenas-Gallegos et al 2015).…”
Section: Discussionsupporting
confidence: 86%
“…After thawing, samples were macerated, homogenized and incubated for 2 hr under moderate agitation with a lysis buffer containing 20 ml PBS (1x), 200 μl Triton X100, 20μL of the 500μL protease inhibitor (Sigma Aldrich, EUA). Subsequently, the material was centrifuged (4°C, 10,000 g) and the supernatant, transferred to new tubes (Souza et al, ). Then acetone (1:9) was added, centrifuged (5 min., 1,000 g, 4°C) and the pellet was solubilized in 0.5 ml PBS (1x).…”
Section: Methodsmentioning
confidence: 99%
“…The mRNA expression level evaluated in technical replicates weresubjected to Shapiro‐Wilk normality test (UNIVARIATE procedure; SAS 9.0 software, SAS Institute Inc., USA). Statistical significances of variables determined in the tissues were assessed with Student‐Newman‐Keuls (SNK) multiple comparisons test ( p < 0.05) (Sousa et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation